Inequality and Economic Growth: Do Natural Resources Matter? - Thorvaldur Gylfason; Gylfi Zoega (Center for Economic Studies and ifo Institute (CESifo), 2002)
This paper is intended to demonstrate, in theory as well as empirically, how increased dependence on natural resources tends to go along with less rapid economic growth and greater inequality in the distribution of income across countries. On the other hand, public policy in support of education can simultaneously enhance equality and growth by raising the return to working in higher technology (that is, nonprimary) industries and thus counter some of the potentially adverse effects of excessive natural resource dependence. Together, these two variables - natural resources and education - can help account for the inverse relationship between inequality and growth observed in cross-country data. Moreover, the analysis highlights the role of public revenue policy. Taxes and fees can be used to reduce the attractiveness of primary-sector employment, lift the marginal productivity of capital in higher technology industries and thus increase the rate of interest and economic growth, while reducing the inequality of income and wealth.
Keywords: 330